PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS PELANGGAN DAN KEPUASAN SEBAGAI VARIABEL INTERVENING - Rendyana Putra; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to determine and analyze the influence of experiential marketing in which sense, feel, think, act and relate to consumer loyalty, know and analyze experiential marketing influences which consist of sense, feel, think, act and relate to customer satisfaction and know experiential influences marketing has an effect on consumer loyalty through McDonald's restaurant customer satisfaction Watugong Malang. The population of this study is that consumers who have come at least one purchase at Mc Donald's Malang amounted to 2,250 while the sample in this study amounted to 96 consumers. Data analysis using Path analysis.The results showed that there was a significant effect of sense, feel, and act on loyalty. While the variables think and relate have no significant effect on loyalty. There is a significant effect of sense, feel, and act on loyalty. Whereas think and relate have no significant effect on loyalty. There is a significant effect of satisfaction with loyalty. Experiential marketing (sense, feel, think, act and relate) has an effect on loyalty not through satisfaction as an intervening variable.Keywords: experiential marketing, sense, feel, think, act, relate, satisfaction and loyalty